Atorvastatin attenuates surgery-induced BBB disruption and cognitive impairment partly by suppressing NF-κB pathway and NLRP3 inflammasome activation in aged mice. (1st March 2021) - Liu, Pengfei; Gao, Quansheng; Guan, Lei; Hu, Yanting; Jiang, Jingwen; Gao, Teng; Sheng, Weixuan; Xue, Xinying; Qiao, Hui; Li, Tianzuo
Abstract: In clinic, perioperative neurocognitive disorder is becoming a common complication of surgery in old patients. Neuroinflammation and blood–brain barrier (BBB) disruption are important contributors for cognitive impairment. Atorvastatin, as a strong HMG-CoA reductase inhibitor, has been widely used in clinic. However, it remains unclear whether atorvastatin could prevent anesthesia and surgery-induced BBB disruption and cognitive injury by its anti-inflammatory property. In this study, aged C57BL/6J mice were used to address this question. Initially, the mice were subject to atorvastatin treatment for 7 days (10 mg/kg). After a simple laparotomy under 1.5% isoflurane anesthesia, Morris water maze was performed to assess spatial learning and memory. Western blot analysis, immunohistochemistry, and enzyme-linked immunosorbent assay were used to examine the inflammatory response, BBB integrity, and cell apoptosis. Terminal-deoxynucleotidyl transferase mediated nick end labeling assay was used to assess cell apoptosis. The fluorescein sodium and transmission electron microscopy were used to detect the permeability and structure of BBB. The results showed that anesthesia and surgery significantly injured hippocampal-dependent learning and memory, which was ameliorated by atorvastatin. Atorvastatin could also reverse the surgery-induced increase of systemic and hippocampal cytokines, including IL-1β, TNF-α, and IL-6, accompanied by inhibiting the nuclear factor kappa-B (NF-κB) pathway and Nucleotide-Binding Oligomerization Domain, or Leucine Rich Repeat and Pyrin Domain Containing 3 (NLRP3) inflammasome activation, as well as hippocampal neuronal apoptosis. In addition, surgery triggered an increase of BBB permeability, paralleled by a decrease of the ZO-1, occludin, and Claudin 5 proteins in the hippocampus. However, atorvastatin treatment could protect the BBB integrity from the impact of surgery, by up-regulating the expressions of ZO-1, occludin, and Claudin 5. These findings suggest that atorvastatin exhibits neuroprotective effects on cognition in aged mice undergoing surgery.